(NlINGWISTIKA TEKSTA I PROBLEMY ANALIZA USTNOJ RE^I (B:s (Nu^EBNOE POSOBIE (B/s - (NfILIPPOW(B, (NkONSTANTIN aNATOLXEWI^s; (NlENINGRADSKIJ GOSUDARSTWENNYJ UNIWERSITETs ((NlENINGRAD (B:s (NiZD(B-(NWO lENINGR(B. (NUN(B-(NTA(B,s, 1989)
(NrEZ(B.: (NNEM(B.s
(NbIBLIOGR(B.: (NS(B. 95-96s
Keywords: (NlINGWISTIKA TEKSTAs; (NtEKST (B((NLINGW(B.) - (NaNALIZs